2018
DOI: 10.1002/hpja.180
|View full text |Cite
|
Sign up to set email alerts
|

In their own words: A qualitative study exploring influences on the food choices of university students

Abstract: Current health promotion nutrition messages were perceived irrelevant given the focus on long-term health risks. Health and adhering to the ADG were not identified as important. The desire to look a particular way was the major influence on food choices. SO WHAT?: While there is an awareness of ADG, our participants made a deliberate decision not to follow them. This provides a challenge for developing relevant preventive health messages for this target audience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 32 publications
5
24
0
6
Order By: Relevance
“…The physical activity module did not require much explanation, asking merely for activity time in minutes. College students are less likely to understand serving sizes and numbers of servings [ 35 - 37 ], which may account for the higher viewership of this presentation.…”
Section: Discussionmentioning
confidence: 99%
“…The physical activity module did not require much explanation, asking merely for activity time in minutes. College students are less likely to understand serving sizes and numbers of servings [ 35 - 37 ], which may account for the higher viewership of this presentation.…”
Section: Discussionmentioning
confidence: 99%
“…There was a disconnect between the holistic view of health of these YA and the usual approaches of health promotion, focussing on specific aspects of health. The YA sentiments on the AGHE echoed previous research where Government nutrition messages often fail to grasp the attention of the public and inspire behaviour change as they are viewed as incorrect, biased and inconsistent [50], or simply not relevant to them [20]. The participants also mentioned conflicting nutrition messages online and on SM as a hindrance to knowing how to eat healthily.…”
Section: Discussionmentioning
confidence: 70%
“…Some of the suggested strategies included making healthy eating cost effective, available in a location convenient to them such as university, and involving friends to make healthy eating a normative behaviour. Whereas in another study, YA were found to want nutrition information related to weight loss and serving size [20]. Previous public health initiatives have focused on promoting knowledge of fruit and vegetables, but have had a low to modest ability to sustain behaviour change [51].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations